Association between visceral adiposity index and kidney stones in American adults: A cross-sectional analysis of NHANES 2007–2018 - Wang, Jiahao; Yang, Zhenzhen; Bai, Yunjin; Yin, Shan; Cui, Jianwei; Xiao, Yunfei; Wang, Jia (Frontiers in Nutrition, 2022)
Objective: To explore the association between Visceral Adiposity Index (VAI) and kidney stones in an American adult population. Materials and Methods: National Health and Nutrition Examination Survey (NHANES) datasets from 2007 to 2018 were used. Participants aged ≥ 20 years who reported kidney stone history and VAI were included. Weighted proportions, multivariable analysis, generalized additive model (GAM) and spline smoothing were used to evaluate the associations between VAI and kidney stones by adjusting gender, age, race, education, marital status, poverty income ratio, smoking, alcohol, high blood pressure, diabetes, congestive heart failure, cancer, vigorous activity, moderate activity, HEI2015 total score, and energy. Results: Totally 13871 American adults were included. All the participants were divided by the VAI into four groups according to the quartile: Q1 (11.96-42.89), Q2 (42.90-74.45), Q3 (74.45-131.43), and Q4 (131.45-611.34). The mean ± standard deviation of the VAI in the four groups were Q1 (29.07 ± 8.22), Q2 (57.53 ± 8.81), Q3 (99.52 ± 16.25), and Q4 (225.92 ± 95.83). In the fully-adjusted multivariable model, VAI was positively correlated with urolithiasis (odds ratio (OR) = 1.001; 95% confidence interval (CI) 1.000 to 1.001). Compared with the first quartile of VAI, the population in the fourth quartile of VAI had a higher prevalence of kidney stones (OR = 1.329; 95%CI 1.104 to 1.600). Subgroup analysis detected no significant interaction effect after adjusting for covariates. Conclusions: The value of VAI is positively correlated with the prevalence of kidney stones, which suggests VAI can be used to assess the potential risk of the prevalence of kidney stones. Key Words: Kidney Stones, VAI, NHANES, Association, Cross-sectional Analysis